2020
DOI: 10.4274/tjps.30633
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophen isolated from endophytic fungi Aspergillus fumigatus strain KARSV04 synergizes the effect of doxorubicin in killing MCF7 but not T47D cells

Abstract: Introduction: Pyrophen, an amino acid-pyrone derivative isolated from Aspergillus fumigatus strain KARSV04 has been reported to exhibit anticancer effect on T47D cells by inhibiting the growth of the cells and modulate the cell cycle on S phase. Present study, effect of pyrophen in the doxorubicin (Dox) chemotherapy on an in vitro model of breast cancers was studied. Methods: The cytotoxicity of pyrophen, doxorubicin and in combination were evaluated in T47D and MCF-7 cells using MTT assay. Modulation on cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…9 Combination of pyrophen fraction of endophyte fungus-doxorubicin showed a synergistic effect in antiproliferative, cell cycle, and apoptotic induction properties MCF-7. 10 However, it remains unclear the effect of Garcinia picrorrhiza fruit ethanolic extract (GpKar) on normal cells except on Vero cells. The combination of doxorubicin and GpKar is expected to be toxic to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…9 Combination of pyrophen fraction of endophyte fungus-doxorubicin showed a synergistic effect in antiproliferative, cell cycle, and apoptotic induction properties MCF-7. 10 However, it remains unclear the effect of Garcinia picrorrhiza fruit ethanolic extract (GpKar) on normal cells except on Vero cells. The combination of doxorubicin and GpKar is expected to be toxic to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the natural product pyrophen (1), a pyrone derivative from Lphenylalanine, was first isolated from Aspergillus niger (Barnes et al, 2003). Pyrophen (1) has been isolated from other Aspergillus species, such as Alternaria alternata (Astuti et al, 2016;Astuti et al, 2020;Hai et al, 2020). This compound has shown anticancer activity, and various studies on its synthesis and biological activity have been previously reported (Reber et al, 2018;Quang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%